Non-invasive method for the assessment of gastric acid secretion - Chiara, Miraglia (Acta Biomed, 2018)
Methods for the measure of gastric acid secretion include invasive and non-invasive tests. The gold-standard to measure the acid output is the collection of gastric after in basal condition (Basal Acid Output, B.A.O.) and after an i.m. injection of pentagastrin (Maximal Acid Output, M.A.O.). However, direct measurement of gastric acid production is out of order in clinical practice, but many GI symptoms are claimed to be related with acid disorders and empirically cured. Hypochlorhydria is associated with precancerous conditions such as chronic atrophic gastritis (CAG). Acid measurement with non-invasive methods (pepsinogens) is supported by international guidelines. (www.actabiomedica.it)